2019
DOI: 10.4269/ajtmh.19-0222
|View full text |Cite
|
Sign up to set email alerts
|

Impact of Dengue Rapid Diagnostic Tests on the Prescription of Antibiotics and Anti-Inflammatory Drugs by Physicians in an Endemic Area in Colombia

Abstract: There is insufficient evidence on whether dengue rapid diagnostic tests (dRDTs) influence clinical decisions in endemic areas. Therefore, our objective was to evaluate the impact of dRDTs on the prescription of antibiotics and antiinflammatory drugs by physicians in a dengue-endemic area in Colombia. A retrospective cohort study was conducted with 330 patients in Cali, Colombia, between January 2012 and December 2017. The exposure was defined by the result of the dRDT. The outcomes were prescription of antibio… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
4
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 7 publications
(5 citation statements)
references
References 28 publications
1
4
0
Order By: Relevance
“…Notably, in both settings, antibiotic prescription decreased to less than half after dengue was confirmed; this finding indicated that the non-specific symptoms or signs of dengue plays a significant role in physicians’ decisions to prescribe antibiotics. Our findings are consistent with previous studies in adults with dengue or acute febrile illnesses, demonstrating that a positive dengue test result can significantly reduce a patient’s likelihood of inappropriately receiving antibiotics in either the outpatient or inpatient setting [ 20 , 21 ].…”
Section: Discussionsupporting
confidence: 92%
“…Notably, in both settings, antibiotic prescription decreased to less than half after dengue was confirmed; this finding indicated that the non-specific symptoms or signs of dengue plays a significant role in physicians’ decisions to prescribe antibiotics. Our findings are consistent with previous studies in adults with dengue or acute febrile illnesses, demonstrating that a positive dengue test result can significantly reduce a patient’s likelihood of inappropriately receiving antibiotics in either the outpatient or inpatient setting [ 20 , 21 ].…”
Section: Discussionsupporting
confidence: 92%
“…While antibiotics may be prescribed inappropriately for conditions that are likely to have a viral etiology, they also may be used in early intervention of febrile illnesses when the pre-test probability of a bacterial infection argues for empirical therapy. The non-specific clinical manifestations of dengue (DENV) overlap with signs and symptoms of other febrile illnesses common to tropical and subtropical zones, such as leptospirosis, for which antimicrobial therapy is therapeutic [ 2 7 ]. At the point of clinical presentation, differentiating dengue from bacterial infections that should be treated with antibiotics may be difficult but also is contextual, depending on the local epidemiology of the respective pathogens [ 8 ].…”
Section: Introductionmentioning
confidence: 99%
“…At the point of clinical presentation, differentiating dengue from bacterial infections that should be treated with antibiotics may be difficult but also is contextual, depending on the local epidemiology of the respective pathogens [ 8 ]. For example, within Thailand, the likelihood of encountering dengue versus leptospirosis differs geographically and pre-test strategies for empirical use of antibiotics in respective locations have been modeled [ 7 , 9 ].…”
Section: Introductionmentioning
confidence: 99%
“…Together, these different factors may not only help in understanding the rising incidence and prevalence rates in our country but also explain the increasingly frequent severe and fatal cases [30] Unfortunately, most of the reported dengue cases in Colombia are diagnosed by clinical criteria, and only a small percentage of the cases are confirmed by Immunoglobulin M (IgM) enzyme-linked immunosorbent assay (ELISA) test or reverse transcriptionpolymerase chain reaction (RT-PCR) (34.7%); only severe or fatal cases are investigated by non-structural protein-1 (NS1) ELISA or RT-PCR [44,45]. For these reasons, some secondary and tertiary care hospitals independently perform rapid diagnostic tests (RDT) for IgM/IgG or NS1 to improve the clinical diagnosis and treatment of cases suspected of dengue [46][47][48]. Despite the widespread use of RDT in Colombia, the few reports evaluating the performance of RDT suggest that a negative result in these tests does not rule out dengue; therefore, clinicians should be aware of dengue diagnosis and confirm cases by laboratory tests [47][48][49][50].…”
Section: Introductionmentioning
confidence: 99%
“…For these reasons, some secondary and tertiary care hospitals independently perform rapid diagnostic tests (RDT) for IgM/IgG or NS1 to improve the clinical diagnosis and treatment of cases suspected of dengue [46][47][48]. Despite the widespread use of RDT in Colombia, the few reports evaluating the performance of RDT suggest that a negative result in these tests does not rule out dengue; therefore, clinicians should be aware of dengue diagnosis and confirm cases by laboratory tests [47][48][49][50].…”
Section: Introductionmentioning
confidence: 99%